Information Technology Changing Performance of Banking Industry-Emerging Challenges and New Potentials - Uppal, R.K. (Gyan Management Journal, 2008)
The severe crises of 1991 gave birth to the new economic thought in the country. A bundle of measures were taken to remove the various deficiencies and rigidities in the Indian economy. Hence, new economic policy was introduced to mould the Indian economy to the right path. Financial sector reforms and bapking sector reforms are the part and parcel of economic reforms, which trengthen the economic reforms. Under the regime of banking sector reforms, IT Act of 1999 gave new dimensions to the Indian banking sector. IT (ATMs, Smart Cards, Internet-B
Keywords: Technology; Banking Industry; Challenges; Potentials